Indonesian Government Policy To Provide Employment Opportunities For Persons With Disabilities - Gumelar, Rachmadani Fatria Agung; Sardi, Martinus (Media of Law and Sharia, 2021)
Persons with disabilities still find it difficult to find and obtain work because they are considered less productive and incapable to work. However, every human being has human rights including the right to obtain work and to persons with disabilities. This study aims to understand the Indonesian government's role based on human rights instruments' concern for work opportunities. The research used a normative study with a descriptive qualitative analysis which is focused on library research and analysis of the compilation of written data. The author found that the role of government is through policies and realization on the program where the direction not only supervision within sanction to the employer but also develop quality and placement of disabilities workforce, open special labor market and promotion to all stakeholder for providing recruitment. Nonetheless, the national government role in the realization of obligation from the human rights legal instruments both international or national still not comprehensively comply with the provision because the specific regulation relates to employment still have discrimination provision, absence of government technical regulation about disabilities employment, lack of regulation and policy measures to encourage private sectors for hire persons with disabilities.